Teknologi Alat Batu Dan Konteksnya Pada Komunitas Gua Gunung Watangan - Indah Asikin Nurani (Balai Arkeologi Yogyakarta, 1996)
In connection with the stone tool technology products, so far research on prehistoric cave life has always been associated with mesolithic technology as a cultural product. Specifically for the main findings from the Sampung site in East Java, a more specific mesolithic culture was found, namely the culture of bone tools. This industry is highlighted by the bone tools products in the form of abundant spatula, stone tools (predominantly non-massive tools), beaded jewelry made of shells, and folded graves. One thing that needs to be questioned here is: do the cultural products of the caves in the East Java region always show the characteristics of the mesolithic culture that have been broadly formulated as mentioned above? This paper will try to display new data that is not in line with these assumptions, namely the Mount Watang Cave Site, which is located in Lojejer Village, Wuluhan District, Jember Regency, East Java. Data obtained from the excavation of Yogyakarta Archaeology Center.